Pemberdayaan Ekonomi Keluarga Melalui Pemanfaatan Teknologi Digital untuk Jual Beli Online - Abdul Gani; Nasrullah; Muhammad Hanafi; Sukranudin; Irwan Yon Hadi; Syamsur Rizal; Ali Karmani (Indonesia, 2025)
This study explores family economic empowerment through the utilization of digital technologies in online trading. The main objective is to examine how digital platforms, particularly e-commerce, influence household income, entrepreneurial participation, and internal family dynamics. The study employs a mixed-methods approach, combining surveys of family households with semi-structured interviews and observational data, to comprehensively analyze the adoption and impact of digital tools on economic outcomes.The results indicate that families engaged in online selling experience significant increases in household income, averaging 30–45%, alongside diversification of business activities and enhanced involvement of family members, particularly women, in decision-making processes. Digital literacy, market accessibility, and community collaboration emerge as critical factors driving successful adoption, while limitations in infrastructure, financial resources, and competitive pressures present notable challenges. The discussion highlights the mechanisms through which digital technologies foster financial inclusion, entrepreneurial skill development, and broader market access, thereby supporting sustainable household empowerment.In conclusion, digital technologies serve as a transformative instrument for family economic empowerment, promoting income growth, business diversification, and social resilience. The study underscores the need for targeted digital literacy programs, infrastructure development, and community support initiatives to maximize the benefits of online trading, providing a practical framework for policymakers and practitioners aiming to enhance household economic sustainability.